Ordered probit analysis of consumers' preferences for milk and meat quality attributes in the emerging cities of Southern India - S. Priyadharsini; G. Kathiravan; M. A. Thirunavukkarasu; W. Ganpat; D. Saravanakumar (Expert journal of marketing, 2017)
In order to assess consumer preferences for milk and meat quality attributes, a study was carried out in two Second-Tier cities of Tamil Nadu. Personal interviews were done to collect the data from 160 respondents chosen through a multistage sampling procedure in each of the two cities selected for this study. Ordered Probit model fitted for the attributes of milk showed that: family size had a significant positive preference towards texture, low fat and low price of milk, educated consumers paid greater attention to taste, safety, flavour, packaging and low fat attributes of milk and low income consumers paid less importance on most of the attributes of milk. Ordered Probit model for meat revealed that as the family size increased, the consumers were likely to give more importance to ageing and tenderness and less importance to leanness of meat. Male consumers paid greater attention to colour and females were none concerned with tenderness, cooking quality and price. As the education level increased, the consumers became more and more quality and price conscious. Households having children paid more importance to tenderness and taste attributes of meat, whereas the household having aged people opted for colour, taste, tenderness, cooking quality, leanness and price attributes. Low income consumers paid less importance to quality attributes and the respondents performing more physical activity paid lesser attention towards leanness and more importance to price of the meat. This suggests the need for enhancing the production of quality livestock products, together by developing a well-organized distribution system.
2758454-9; 2344-6773; Expert journal of marketing; 778946770